A Case of Cystic Basal Cell Carcinoma Which Shows a Homogenous Blue/Black Area under Dermatoscopy. (14th September 2010) - Yoneta, Akihiro; Horimoto, Kohei; Nakahashi, Keiko; Mori, Satoru; Maeda, Kazuo; Yamashita, Toshiharu
Abstract : Basal cell carcinoma (BCC) is the most common skin tumor and contains several different histopathological types. Here, we report a case of cystic basal cell carcinoma, which is relatively rare and might be clinically misdiagnosed. A dermatoscopic examination of the case revealed a homogenous blue/black area usually not seen in BCC. We reviewed 102 BCC cases resected and diagnosed at Sapporo Medical University Hospital between April 2005 and March 2010. Among them, only three were the cystic type.